India Ombudsman: Structural-Institutional and Functional Aspect - Aaqil Zauqi (Global Writing Academica Researching and Publishing, 2023)
The ombudsman is a concept belonging to the public administration in general and defends and protects citizens who are violated of their rights and powers against state institutions. The ombudsman, which finds areas of application at different levels of development in all continents of the world, is also applied in Asia. The purpose of this article is to provide information on the structural-institutional and functional aspects of the Asian Indian Ombu. In this context, the place and importance of the ombudsman for Indian democracy and public administration should be underlined.